Can Immigrants Insure against Shocks as well as the Native-born? - Asadul Islam; Steven Stillman; Christopher Worswick (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
The impact that an unforeseen event has on household welfare depends on the extent to which household members can take actions to mitigate the direct impact of the shock. In this paper, we use nine years of longitudinal data from the Household Income Labour Dynamics of Australia (HILDA) survey to examine the impact of job displacement and serious health problems on: individual labour supply and incomes, household incomes and food expenditure. We extend on the previous literature by examining whether mitigation strategies and their effectiveness differs for the native-born and immigrants. Immigrants make up nearly one quarter of the Australian population and there are a number of reasons to suspect that they may be less able to mitigate adverse shocks than the native-born.
Keywords: J65; I31; J15; 330; job loss; income; consumption; labour supply; disability